CROSSING TRANSPORT IN THE PERSPECTIVE OF SHIP CAPACITY AND PORT OPERATOR COMPETENCE - Ahmad Fauzi; Mahbub Arfah (Jurnal Maritim Malahayati, 2023)
The implementation of ferry transportation must be able to ensure the comfort, security and safety of passengers and goods. Port management officials and ship operators are the main stakeholders in improving safety. The lower supervision led to higher accident potential. Supervision to safety can only be carried out by operators with appropriate competence. This research uses descriptive quantitative method. Descriptions are carried out on symptoms or phenomena related to ships, productivity, port operators and ship certificates. Through this research, it is known that the passenger carrying capacity of the ship from Bira to Pamatata has a surplus, but the vehicle carrying capacity is known to be minus so that the vehicle loading space is always full when sailed. Based on the Value Range and Qualification table, it is known that port processing is in the category of very threatening shipping safety because port operators do not yet have competence if measured based on the certificate they have. All operating ships have a complete ship certificate in accordance with applicable regulations